PROBLEMS OF SMALL ENTERPRISES OF THE BAKING INDUSTRY IN THE KEMEROVO REGION - Menkh L.V.; Rumyantseva E.E. (Техника и технология пищевых производств)
Modern bakery industry predominantly consists of small and medium enterprises, which are supported by the state. It is a serious infrastructure that needs constant development and improvement. Resources of small and me-dium business are limited, which hinders the development of the entire industry. The current state of the baking in-dustry in the region and the role of small and medium-sized enterprises in the development of the baking industry have been investigated. The geographical distribution of small bakeries and their quantity in the cities of the Keme-rovo region have been presented. The structure of bakery products produced by small enterprises of the region and disadvantages of the use of the simplified production technology using baking powder instead of yeast has been analyzed. The main trends in the development of small business in the region and the perspective directions of governmental support have been described. Providing a significant increase in the quantity and quality of the produce of small manufacturing and export-oriented enterprises is one of the priorities of the regional policy in the development of small and medium business in the Kemerovo region.